2005
DOI: 10.1111/j.1423-0410.2005.00715.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing factor VIII activity in frozen plasma

Abstract: For an optimal yield of FVIII, freezing should start within 4 h after plasma donation. We propose the use of the term 'ice front velocity' instead of 'freezing speed', taking into consideration that the volume and shape of plasma containers may differ. We found only a marginal loss of FVIII:C when the ice front velocity was 26 mm/h or faster, but a significant loss when it was 9 mm/h or slower. We recommend freezing times of 60 min or shorter. We were not able to demonstrate any eutectic point in human plasma.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 17 publications
(48 reference statements)
0
26
0
Order By: Relevance
“…Source plasma units frozen completely within 1 hour to a core temperature below −30°C contained significantly greater levels of FV and FVIII than plasma units frozen more slowly at −30°C in large walk‐in freezers, which takes several hours to reach a core temperature of −30°C . FVIII recovery in 100‐mL plasma aliquots decreased by 7% when the freezing time was prolonged from 1 to 4 hours and by 27% when freezing time was prolonged up to 24 hours . The difference between FVIII levels in source plasma units frozen at −30 and at −20°C in industrial‐size chambers was 12.6% .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Source plasma units frozen completely within 1 hour to a core temperature below −30°C contained significantly greater levels of FV and FVIII than plasma units frozen more slowly at −30°C in large walk‐in freezers, which takes several hours to reach a core temperature of −30°C . FVIII recovery in 100‐mL plasma aliquots decreased by 7% when the freezing time was prolonged from 1 to 4 hours and by 27% when freezing time was prolonged up to 24 hours . The difference between FVIII levels in source plasma units frozen at −30 and at −20°C in industrial‐size chambers was 12.6% .…”
Section: Discussionmentioning
confidence: 98%
“…13 In two studies PC was reduced by 5 and 6%, respectively, when PF24 and PF24RT were compared with FFP. 9,12 Cardigan and colleagues 7 has been the only study group that found considerably lower fibrinogen, FV, and FXI levels in PF24 than in FFP (12,15, and 7%, respectively). Others have failed to observe such differences when PF24 or PF24RT was compared with FFP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown previously that the time taken to freeze plasma can affect the resulting FVIII activity; a small difference was recorded between freezing times of 1 and 4 hours. 13 Taken together these minor differences may have contributed to the improved FVIII activity seen in the QC data compared to the validation data. Of note, it is the QC data that are reflective of the products used in Canadian hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…FVIII activity in plasma was found to be stable to prefreezing room temperature holds of up to 4 hours. Rapid freezing to a core temperature of −30°C within 60 minutes, as compared to slow freezing over 24 hours, resulted in mean FVIII recoveries of 93.6 versus 68.2% [69]. Runkel et al pooled and split whole blood donations, generating plasma within 8 hours of phlebotomy that was frozen at the 8-hour time point or held at either ambient or refrigerated temperatures for an additional 16 hours prior to freezing [70].…”
Section: Overview: Assessing the Quality Of Transfusable Plasmamentioning
confidence: 99%